Role of vitamin D in iron metabolism, a pilot study - Pandey, Uma; Divakar, Hema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to evaluate the effect of Vit D & Iron supplementation on Serum Hb level &Vit D level as compared to Iron supplementation alone. To evaluate the percentage responders in terms of Haemoglobin to Iron supplementation when Vit D is added as compared to only Iron supplemented. Vitamin D Deficiency is very prevalent in our country due to many reasons; therefore we also wanted to assess how deficient they are? Methods: Recruited pregnant mothers were with 25 (OH) D <20ng/ml & Hb=8-10g/dl. Patients were randomized into groups using a computerized program. Group iron + Vitamin D : tablets containing fixed dose combination of vit D (1000 IU) + ferrous ascorbate (100mg of elemental iron) + folic acid (1 mg) + vit B12 (7.5 mcg) (1 tab/day) for 12 weeks. Group iron alone: tablets containing fixed dose combination of ferrous ascorbate (100 mg of elemental iron) + folic acid (1.1 mg) (1 tablet/day) for 12 weeks. Results: There was no significant difference between the ages of patients of two groups. Parity and BMI were nearly same. Vit D level assessment at the recruitment in both groups is nearly same and also Hb level assessment at the recruitment in both groups is nearly same. The study shows that addition of Vitamin D to the Iron supplement does not increase the level of Hb any further as compared to the Iron administration alone. Conclusions: This pilot study shows that administration of iron to Vitamin D does not influence the rise in haemoglobin level any greater than Iron administration alone. A larger sample size study is needed to prove this finding further.